Communicating climate change to farmers using the mental models approach in identifying the information needs of a rice farming village in Bayambang, Pangasinan, Philippines - Francisco, Rosa Pilipinas F.; Tirol, Ma. Stella C. (2010)
The mental models approach was used to identify the climate change information needs of farmers in a rice farming village in the Philippines. Four semi-constructed interviews with scientists and 18 open-ended interviews with rice farmers were conducted. Based on the scientists' model, the climate change concepts relevant to rice farmers were the human activities that contribute to climate change, the effects of climate change on the growth of the rice crop and on rice farming, and the possible adaptation strategies. The rice farmers' mental models on climate change were incomplete and not well defined. Most of the correct but imprecise beliefs and knowledge gaps were about the causes of climate change and the specific effects of climate on the growth of rice crop. The rice farmers knew of adaptation strategies that they had traditionally used but were unaware of other adaptation strategies. Content of risk communications addressed to rice farmers were provided as part of recommendations.
Keywords: Climate change; Climate change risk management; Effect of climate on human beings